The digital economy: Insight from a special survey with IT service exporters - Wei Dong; James Fudurich; Lena Suchanek (Bank of Canada, 2016)
Information technology (IT) is an increasingly integral part of everyday business and personal life reflecting the ongoing and accelerating digital transformation of the economy. In this paper, we present information gathered from a survey with export-oriented firms in the Canadian IT service industry and consultations with industry associations aimed at shedding light on this small but highly dynamic sector. Our main findings from this survey are: (i) IT service firms experience strong sales growth and tend to be very positive about their outlook, driven by the solid exports that comprise the majority of their sales; (ii) in this context, firms overwhelmingly view the weaker Canadian dollar as favourable, boosting their margins on foreign sales; (iii) because of the knowledge-intensive nature of the industry, firms report investing in human capital more than in physical capital. This often comes with strong employment and R&D investment intentions, although firms in some regions face difficulties in recruiting qualified staff. The survey results provide initial insight in the context of our broader agenda to better understand the implications of digitalization for the Canadian economy.
Keywords: D22; L86; O33; 330; Firm dynamics; Service sector